(untitled) (Journal of Human Sciences, 2023)
Those in charge of special education in the preparatory stage in Qur’anic schools seek to achieve many scientific and educational competencies, by focusing on teaching the Holy Qur’an first and then the Arabic language, in order to provide the child with the skills of recitation, the rules of intonation, mastery of various letters, and have the ability to read and write Arabic words fluently, so how about if These competencies came together in a one methodology that serves the two goals, Hence, the importance of this research appears, in which it relied on the analytical descriptive approach for the nature of the study. The first section included the definition of the methodologies of teaching the child in the level of Pre School, while the second section dealt with the definition of the methodology of Fath al-Rahman, and in the end a conclusion containing the most important results and recommendations.